Effects of a coherent mode on the redistribution of divertor particle flux in HL-2A H-mode plasmas. (17th May 2021) - Wu, N; Cheng, J; Yan, L W; Huang, Z H; Xu, J Q; Wang, W C; Ke, R; Yang, Z C; Ji, X Q; Liu, L; He, X X; Jiang, M; et al.
Abstract: The effects of a coherent mode (CM) at a frequency of f = 13–16 kHz on the redistribution of divertor particle flux have been studied in HL-2A H-mode plasmas using multiple diagnostics. The experimental results demonstrate that a CM localized at the middle of the pedestal results in outward particle transport, limiting the growth of the pedestal density gradient in the recovery phase of the pedestal, leading to a substantial increase in the localized particle flux striking the outer divertor target, which clearly deviates from the primary peak at the strike point. These observations indicate that the CM might play a crucial role in redistributing the divertor particle flux, which is important for understanding and controlling the divertor heat flux in future fusion-relevant devices.